2019
DOI: 10.1021/acs.jafc.9b04613
|View full text |Cite
|
Sign up to set email alerts
|

16α-Hydroxytrametenolic Acid from Poria cocos Improves Intestinal Barrier Function Through the Glucocorticoid Receptor-Mediated PI3K/Akt/NF-κB Pathway

Abstract: This study evaluated the effect of triterpenoids from edible mushroom Poria cocos on intestinal epithelium integrity and revealed the transcriptional regulatory pathways that underpin restorative mechanisms in the gut. Based on computational docking studies, transcriptional activation experiments and glucocorticoid receptor (GR) protein immunofluorescence localization assays in cultured cells, 16α-hydroxytrametenolic acid (HTA) was discovered as a novel GR agonist in this study. HTA ameliorates TNF-α-induced C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…11 It could also protect against cerebral ischemia injury by targeting PI3K/Akt pathway. 10 Also, PA enhanced melatonin by inhibition of AKI-to-CKD transition through mediating growth arrest-specific 6 and nuclear factor-erythroid-2-related factor 2 (Gas6/Nrf2) axis. 10 Another study showed that PA impaired glucose metabolism and stimulated mitochondrial apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 It could also protect against cerebral ischemia injury by targeting PI3K/Akt pathway. 10 Also, PA enhanced melatonin by inhibition of AKI-to-CKD transition through mediating growth arrest-specific 6 and nuclear factor-erythroid-2-related factor 2 (Gas6/Nrf2) axis. 10 Another study showed that PA impaired glucose metabolism and stimulated mitochondrial apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…10 Also, PA enhanced melatonin by inhibition of AKI-to-CKD transition through mediating growth arrest-specific 6 and nuclear factor-erythroid-2-related factor 2 (Gas6/Nrf2) axis. 10 Another study showed that PA impaired glucose metabolism and stimulated mitochondrial apoptosis. 8 In the present study, the alterations of Bax and Bcl-2 were reversed by PA treatment, suggesting that PA suppressed cell apoptosis in rats with lung injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Ginsenoside Rg1, also one of the main constituents of Panax ginseng, and its metabolites could inhibit colitis [15]. 16α-hydroxytrametenolic acid from Poria cocos improved intestinal barrier function [16]. Yam polysaccharide from Dioscorea opposita reduced in ammation in the rat model of colitis induced by TNBS [17].…”
Section: Introductionmentioning
confidence: 99%
“…Effects on the Gut.Studies showed that Poria had a protective effect on the intestinal tract. 16α-hydroxytrametenolic acid (6) could improve intestinal barrier function through glucocorticoid receptor-mediated PI3K/ Akt/NF-κB pathway, suggesting that 16α-hydroxytrametenolic acid could strengthen the intestinal barrier[96]. Xiao et al study showed that the alcohol extract of Poria could inhibit intestinal contraction in vitro by blocking the M receptor and regulate intestinal peristalsis function, which provided a new theoretical basis for the treatment of diarrhea type IBS…”
mentioning
confidence: 99%